On beauty of artworks as aesthetic true representations of reality : a collection of pragmaticist inquiries into the epistemology of artistic creation and evaluation of artworks /: a collection of pragmaticist inquiries into the epistemology of artistic creation and evaluation of artworks. (2022) - Nesher, Dan
No abstract available